2018
DOI: 10.11158/saa.23.8.11
|View full text |Cite
|
Sign up to set email alerts
|

Life table and predation rate of Amblyseius swirskii (Acari: Phytoseiidae) fed on Eotetranychus frosti (Tetranychidae) and Cenopalpus irani (Tenuipalpidae)

Abstract: The life history and predation rate of Amblyseius swirskii Athias-Henriot feeding on Eotetranychus frosti (McGregor) (Tetranychidae) or Cenopalpus irani Dosse (Tenuipalpidae) were determined at 25±1°C, with 16:8 h L: D, at an average daily relative air humidity of 60±10% on apple leaves. A. swirskii successfully completed development, oviposition, and survival on both diets. Individuals of predator reared on E. frosti prey showed improved performance as compared to C. irani prey. The results indicated that its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In our previous study, life history and predation parameters demonstrated that A. swirskii is able to feed and complete its development on E. frosti and C. irani; likewise, this predator can exhibit a high potential for population increase when fed on both pest mites (Bazgir et al, 2018). Results of the present study confirmed this.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our previous study, life history and predation parameters demonstrated that A. swirskii is able to feed and complete its development on E. frosti and C. irani; likewise, this predator can exhibit a high potential for population increase when fed on both pest mites (Bazgir et al, 2018). Results of the present study confirmed this.…”
Section: Discussionsupporting
confidence: 87%
“…In an earlier study, it was shown that A. swirskii has a high capacity of development and population growth when fed on the two pest species; E. frosti and C. irani (Bazgir et al, 2018). A critical step in determining the ability of A. swirskii to regulate E. frosti and C. irani is to assess its functional response and consumption rate when offered these preys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a clear distinction between type II and III based on predation is rather di cult [7]. Many published results reported that type II is the commonly frequent type among predators, especially, among predaceous mites belonging to the family Phytoseiidae [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A type II functional response is common in phytoseiid mites (Afshar & Latifi 2017;Alfaia et al 2018;Barbosa et al 2019). Phytoseiid predators with a type II functional response, such as Neoseiulus californicus McGregor, Neoseiulus cucumeris Oudemans, Neoseiulus barkeri Hughes and Amblyseius swirskii Athias-Henriot, were proved to be efficient for control of pest organisms, especially at low prey densities (Koehler 1999;Jafari et al 2012;van Lenteren 2012;Calvo et al 2015;Song et al 2016;Patel and Zhang 2017;Akyazi & Liburd 2019;Bazgir et al 2020). The attack rate and handling time determine the magnitude of the functional response (Pervez & Omkar 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The attack rate and handling time determine the magnitude of the functional response (Pervez & Omkar 2005). Female A. andersoni response to A. pallida included a higher attack rate (5.961) and a shorter handling time (0.014 d) than other phytoseiid biocontrol agents, such as A. swirskii to Eotetranychus frosti McGregor eggs (0.1142, 0.4858h) (Bazgir et al 2020), and Neoseiulus womersleyi Schicha to Tetranychus urticae Koch eggs at 25℃ (5.467, 0.056 d) (Sugawara et al 2018 handling time (T/T h ) (Fathipour et al 2017). As the handling time decreased, predation capacity during one day increased.…”
Section: Discussionmentioning
confidence: 99%